50 shades of hacking: How IT and cybersecurity industry actors perceive good, bad, and former hackers. Issue 1 (2nd January 2020) - Tanczer, Leonie Maria
ABSTRACT: The hacker is the epitome of a cybersecurity threat and the embodied misuse of the Internet. However, in recent years, notions of hacking have begun to change. Blurred boundaries mark the term, best expressed in its overlap with "security researcher." This article draws on a 3.5-year research project on the hacker community and applies an international political sociology framework to uncover routines of rationalization. Interviews with IT and cybersecurity industry experts expose accepted identities, practices, and behaviors of hackers, which allows for the construction of in-group and out-group members in the IT and cybersecurity field. Additionally, the empirical findings are used to propose a conceptual framework (the Möbius strip ) to situate the moral valence of hackers on a flexible model. Thus, the article provides insight into the ontological and normative complexities that define the study of hackers, as well as the perception of IT and cybersecurity professionals.